Isolation of Campylobacter jejuni and Campylobacter coli from the gall bladder samples of sheep and identification by polymerase chain reaction - Ertas, HB; Özbey, G; Kiliç, A; Muz, A (Wiley, 2003)
In this study, 100 gall bladder samples of sheep slaughtered at an abattoir in Elazig province were examined for Campylobacter jejuni and Campylobacter coli by culture and polymerase chain reaction (PCR). Preston Campylobacter Agar supplemented with 7% horse blood and Preston Selective Supplement (Oxoid, Hampshire, UK) were used for isolation of the agents. Campylobacter spp. were isolated in 66 samples, and they were identified as 34%C. jejuni and 32%C. coli. A multiplex PCR based upon the use of ceuE gene-specific primers was applied on DNA samples extracted from C. jejuni and C. coli isolates. All C. jejuni and C. coli strains that were positive by culture were also detected to be positive by PCR. This study shows that PCR can be used an alternative, rapid and sensitive test for the identification of C. jejuni and C. coli which threaten human and animal health.
Keywords: Rapid Identification; Pcr; Helicobacter; Milk; Arcobacter; Outbreak; Homology; Probes; Assay; Spp.